Newer Hemostatic Agents Used in the Practice of Dermatologic Surgery - Jill Henley; Jerry D. Brewer (Dermatology Research and Practice)
Minor postoperative bleeding is the most common complication of cutaneous surgery. Because of the commonality of this complication, hemostasis is an important concept to address when considering dermatologic procedures. Patients that have a bleeding diathesis, an inherited/acquired coagulopathy, or who are on anticoagulant/antiplatelet medications pose a greater risk for bleeding complications during the postoperative period. Knowledge of these conditions preoperatively is of the utmost importance, allowing for proper preparation and prevention. Also, it is important to be aware of the various hemostatic modalities available, including electrocoagulation, which is among the most effective and widely used techniques. Prompt recognition of hematoma formation and knowledge of postoperative wound care can prevent further complications such as wound dehiscence, infection, or skin-graft necrosis, minimizing poor outcomes.